Can Institutional Ownership Moderate Green Accounting, Capital Intensity, Deferred Tax Burden on Effective Tax? - Elsa Fauzia; Januar Eky Pambudi; Hendra Galuh Febrianto (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to analyze the influence of institutional ownership on a company's effective tax rate by considering green accounting, capital intensity, and deferred tax expense. Using secondary data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023, this quantitative research applies purposive sampling to select samples from a population of 219 firms. Data were obtained from sustainability and annual reports. The findings reveal that green accounting and deferred tax expense significantly affect the effective tax rate, while capital intensity does not. Furthermore, institutional ownership moderates the effects of green accounting and deferred tax expense on the effective tax rate but does not moderate the effect of capital intensity. These results have practical implications for companies aiming to design more efficient tax strategies, and for investors evaluating corporate tax policies before making investment decisions. From a regulatory perspective, the findings offer valuable insights for creating tax policies that enhance corporate transparency and accountability. The study presents novelty by simultaneously examining green accounting, capital intensity, and deferred tax expense with institutional ownership as a moderating variable—an approach rarely applied in the manufacturing sector. This combination offers new perspectives on the interrelation between environmental practices, asset structure, tax planning, and investor influence. Institutional ownership, in particular, highlights how shareholders can play a role in shaping sustainable and transparent corporate tax policies.